Improving Students Ability in Using Preposition of Place Through Video as Media - Rahayuningsih, Yuni (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
In learning English, grammar is one of significant components to mediate the system of written symbol that cannot be avoided. Tenses, preposition, to be, and articles are some aspect of grammar. Preposition is one of the important things in grammar aspects. The formulation of problem in this research is “Can video as media develop student’s ability in using preposition of place?”. The research design in this research is quasi experimental design. The sample of this research is students in SMK TUNAS RAJAWALI and the writer taken all students the tenth grade is 26 students. The first step of this research the writer gave pretest to measure the student abilities before doing treatment. Second give treatment the teacher usually starts the lesson by greeting the students and checking the attendance list. It is support by the result of the using this method that the teacher always greets the student when they start the lesson. The activities during the teaching and learning process the classroom. Then the teacher showing the video about preposition of place to the student’s, the teacher ask the student’s to watch the video about the material preposition of place, the teacher ask the students to repeat each the sentences of preposition, after that the teacher ask the students to understand the kinds of preposition of place. The last is the teacher asking the student’s feeling about teaching and learning process of preposition of place by using video. By using t - test formulation the writer gets 16.158 and the t-table value with 0.05 with df 25 is 1.7081. It means that t-test value is higher than t-table. In other word it can be said that the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It means that the student’s ability before gave video as media is low and the student’s ability after teach using video as media technique is improve, so the video as media is effective for the tenth-grade students of SMK TUNAS RAJAWALI.